ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN ATAU NASABAH DALAM MEMILIH BANK SEBAGAI TEMPAT MENABUNG DI YOGYAKARTA - Galih Widhiyanto; Hendro Setyono (Jurnal Fokus Manajemen Bisnis, 2015)
This study aims to determine the effect of multipurpose networks ATMs, interest, administrative fees, bank locations and bank services the customer's decision in choosing a bank as a place to save in Yogyakarta. In this study, taking a sample of residents who live in the city Yogyakarta with 60 respondents. This testing using analysis tools in the form of correlation (validity test) and reliability test for know the validity of the data used in research. To test the hypothesis in this research is multiple regression test. In the F test obtained F count (27.594)> F table (2.28) which means that together there is a significant influence between the variable services,Â  bank locations, multipurpose ATM networks, bank interest and administrative fees towards decisions. In the t test there are three variables that have no effect significantly to customer savings decisions, namely service variables with a value of t arithmetic (1.385) <t table (2.0057), Bank Location with a value of t arithmetic (1,933) <t table (2.0057) and Multipurpose And ATM Networks with calculated t values (0.839) <t table (2.0057). While interest and administrative costs are partial each has a significant effect on the savings decision variable customers because the t value obtained for the bank interest (3,697)> t table (2.0057) and administrative costs (3,510) > t table (2.0057). The results of this study provide evidence that 71.9% of customers' savings decisions influenced by the variable service, bank location, multipurpose ATM networks, bank interest and administrative costs while the remaining 28.1% influenced by other factors. Based on data analysis, the factors are a big influence on customer savings decisions is bank interest.